Reduced CD27−IgD− B Cells in Blood and Raised CD27−IgD− B Cells in Gut-Associated Lymphoid Tissue in Inflammatory Bowel Disease - Pararasa, Chathyan; Zhang, Na; Tull, Thomas J.; Chong, Ming H. A.; Siu, Jacqueline H. Y.; Guesdon, William; Chavele, Konstantia Maria; Sanderson, Jeremy D.; Langmead, Louise; Kok, Klaartje; Spencer, Jo; Vossenkamper, Anna (Frontiers in immunology, 2019)
The intestinal mucosa in inflammatory bowel disease (IBD) contains increased frequencies of lymphocytes and a disproportionate increase in plasma cells secreting immunoglobulin (Ig)G relative to other isotypes compared to healthy controls. Despite consistent evidence of B lineage cells in the mucosa in IBD, little is known of B cell recruitment to the gut in IBD. Here we analyzed B cells in blood of patients with Crohn's disease (CD) and ulcerative colitis (UC) with a range of disease activities. We analyzed the frequencies of known B cell subsets in blood and observed a consistent reduction in the proportion of CD27 IgD B cells expressing all Ig isotypes in the blood in IBD (independent of severity of disease and treatment) compared to healthy controls. Successful treatment of patients with biologic therapies did not change the profile of B cell subsets in blood. By mass cytometry we demonstrated that CD27 IgD B cells were proportionately enriched in the gut-associated lymphoid tissue (GALT) in IBD. Since production of TNFα is a feature of IBD relevant to therapies, we sought to determine whether B cells in GALT or the CD27 IgD subset in particular could contribute to pathology by secretion of TNFα or IL-10. We found that donor matched GALT and blood B cells are capable of producing TNFα as well as IL-10, but we saw no evidence that CD27 IgD B cells from blood expressed more TNFα compared to other subsets. The reduced proportion of CD27 IgD B cells in blood and the increased proportion in the gut implies that CD27 IgD B cells are recruited from the blood to the gut in IBD. CD27 IgD B cells have been implicated in immune responses to intestinal bacteria and recruitment to GALT, and may contribute to the intestinal inflammatory milieu in IBD.